"No piracy talk": how online brand communities work to denormalize controversial gaming practices. Issue 4 (22nd April 2020) - Scaraboto, Daiane; Almeida, Stefânia Ordovás de; dos Santos Fleck, João Pedro
Abstract : Purpose: The purpose of this study is to explain how online brand communities work to support the denormalization of controversial (i.e. illegal yet normalized) gaming practices. Design/methodology/approach: This qualitative study was characterized by long-term immersion in an online brand community for Brazilian Xbox gamers. The dataset includes online and offline interactions with community members, interviews, and online archival data. Findings: This study shows how online brand community members promoted legal gaming in a market where piracy was prevalent. It demonstrates how community members worked to establish coherence; engaged in cognitive participation; developed collective action that extended beyond the community; and reflected on their own work. Research limitations/implications: This study identifies online brand communities as a potential ally in combating controversial practices in online gaming; complements individual and behavioral approaches in explaining why consumers adopt controversial practices in online environments; and adds a normalization framework to the toolkit of Internet researchers. Practical implications: This study identifies ways in which the potential of online brand communities can be leveraged to reduce consumer adherence to controversial gaming practices through denormalizing these and normalizing alternative practices that may be more desirable to companies and other stakeholders. Originality/value: This long-term, qualitative study inspired by normalization process theory offers an innovative perspective on the online practices of consumers who engage with a brand in ways that create value for themselves and for the brand.